Online child sexual abuse: an Indian perspective - Rajput, Balsing (Springer series on Asian criminology and criminal justice research, 2024)
"This book discusses the phenomenon of child sexual abuse material (CSAM), in the context of the Indian law enforcement and criminal justice system. It helps readers understand the complexities involved in these types of online crimes, and the perspectives of various stakeholders involved in the investigation and justice process. This volume analyzes the unique challenges faced by law enforcement when dealing with cybercrime, and specifically when the victims are minors. Representing a unique analysis of the surge of child sexual abuse material on the internet during COVID-19 pandemic lockdowns, this book discusses cybercrime and societal behavior patterns. With practical remedial steps to control and preclude online child sexual abuse, this volume will be of interest to law enforcement, researchers, and child protection advocates in India and other developing digital economies." --